Gender Equality on Education Issues in UN Women’s Article: “Leaving No Girl Behind in Education” - Budi Santoso; Dina Muthmainnah; Lishapsari Prihatini; Siti Lady Havivi; Rahman Hakim (Interdisciplinary Social Studies, 2025)
Gender equality is a global concern as gender points are listed in Sustainable Development Goal (SDG). UN Women is a UN organization dedicated to gender equality and women's empowerment. Their activities collaborate closely with social media to advance women's rights. An article entitled "Leaving No Girl Behind in Education," published by UN Women on 11 October 2022, discusses the issue of gender equality in the education field. Applying Robert M. Entman's framing model to analyze. It shows that the article addressed the gender gap in education and careers and expanded access to education for girls from disadvantaged backgrounds. The reasonings behind the issue stated in the article are among others; the incapability in economic, the significant difference, discrimination and relegation in the country area, the impact of the Covid-19 pandemic, poor resources, gender issues, and regional liability. The recommendations include ensuring equal access to education for all girls, providing adequate resources to mitigate the impact of the pandemic on girls' education, and encouraging girls' participation in technology to achieve gender equality and empower them. The problem-solving strategies proposed in the article involve increasing investment in girls' education, addressing discrimination and barriers, mitigating the impact of the COVID-19 pandemic, promoting gender equality in STEM education and careers, and fostering global partnerships and commitment.